Table of Content - - (Journal of Economic, Administrative and Legal Sciences, 2023)
Table of Content: 1. Innovation and its role in industrial excellence and the development of logistics services in KSA Dr. Vivian Mohammed Saleh Nasrulddin, Mrs. Tharaa Hassan Omar Alidrisi 2. The Moderating role of Information Technology in the relationship between the Re-Engineering of Administrative Processes and The Institutional Performance of the Yemeni General Electricity Corporation (2018-2022) Mr. Munif Ahmed Saif Al-Muhrami , Prof. Nahg AbdulMajid Alawi 3. The Impact of Applying Governance Mechanisms on Corporate Social Responsibility Disclosure in Saudi Banks Co-Prof. Maha Faisal Alsayegh, Mrs. Nawal Mohammed Aljuaid 4. The legal system for threatening fines in civil lawsuits according to the Saudi system Dr. Randa Mustafa Hassan Suliman 5. The extent to which health insurance indicates the efficiency of healthcare centers in KSA Dr. Vivian Mohammed Saleh Nasrulddin, Mrs. Amal Ghazi Alnahdi, Mrs. Esraa Ahmad Bokhari 6. The reality of brainstorming among students of the Academic Complex of Al-Mahalla Colleges at King Khalid University and the importance of strategic planning in its development Asst-Prof. Reda Abdelfattah Ibrahim Mohamed, Co-Prof. Ehsan Ibrahim Allah Gabu Ibrahim 7. The touristic values of Jordan pavilion at Expo 2020 Dubai and its most prominent challenges from visitors’ standpoint Mrs. Suad Fayez Malkawi 8. Analysis of the performance of Khartoum Customs Department during the period 2019-2021 Dr. Akram Abd Eldaim Mohammed